Homeopathy in the brazilian public health system in the last 15 years (Research, Society and Development, 2022)
The general objective of this article was to carry out a survey on the use of homeopathy in the Brazilian public health system in the last 15 years. An integrative literature review was carried out using the following databases: Scielo (Scientific Electronic Library Online), LILACS (Latin American and Caribbean Literature on Health Sciences), VHL (Virtual Health Library) and PubMed (National Library of Medicine). ), articles from the last 15 years, where the search period was between December 2021 and February 2022. It was identified that 17% (2/12) of the studies interviewed students in the area and health professionals working in homeopathy at UBS for the purpose of to know about knowledge of homeopathy and performance in this area. 58% (7/12) of the works carried out interviews with users. Additionally, 25% (3/12) of the studies conducted interviews with municipal and state managers to assess their knowledge about homeopathy and the National Policy on Integrative and Complementary Practices (PNPIC). In this way, homeopathy is one of the Integrative and Complementary Practices (PIC) that went through a long process for inclusion in the Brazilian public system, in comprehensive health care it is essential to report that there is also a need for public encouragement, not only from the private sector, in the training of medical and pharmaceutical professionals who understand the importance of this PIC, as well as the others provided for in the PNPIC in the SUS.